Caroline: project 2. Transition in escapism / Mohamad Noor Azri Yusri - Yusri, Mohamad Noor Azri (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
The design intention is to design an escape portal that represents how Caroline acts to free herself from her other parents who want her to stay in the other world.